VALIDASI AHLI TERHADAP BUKU AJAR PROJEK IPAS UNTUK PESERTA DIDIK FASE E - Ami, Mucharommah Sartika; Yanti, Norma Linda (Universitas Tanjungpura, 2024)
The IPAS Project for phase E students at vocational high school is a project-based subject that integrates natural and social sciences to explain phenomena in life scientifically. IPAS Project learning should use project-based learning methods. Project-based learning needs to be supported by learning media such as textbook. This research was conducted to describe the suitability of the IPAS Project textbook based on the expert validation. The research method used is development research which refers to the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). In this research, the stages carried out were analyze, design, and develop. Researchers used validation sheets which prepared based on the expertise of each validator. The data that has been collected is scores and suggestions from the three validators. The score data from each validator was calculated as an average percentage and then interpreted into four categories: very worthy/very good, decent/good, less worthy/sufficient, or not worthy/inadequate. The results show that the IPAS Project textbook developed meets the very worthy/very good category with the percentage of material expert, learning media expert, and teacher respectively being 79,2%; 80,0%; and 95,3%. These results indicate that the textbook developed can be used by stage E students.